Sedation With Xylazine Hydrochloride Decreases the Stress Response in Merino Meat Sheep During Routine Hoof Trimming in a Tilt Table - Amin, Safaa; Wagner, Romy; Fieseler, Helena; Rizk, Awad; Schmicke, Marion; Spilke, Joachim; Mielenz, Norbert; Baumgartner, Walter; Schären-Bannert, Melanie; Starke, Alexander (Frontiers in Animal Science, 2022)
We hypothesized that the hoof trimming in sheep in dorsal recumbency implicates a short but intensive stress situation and that the sedation with xylazine causes a decrease in the stress response in this situation. Ten healthy female merino meat sheep were randomly divided in two groups receiving either xylazine hydrochloride (0.1 mg/kg BM applied intramuscularly) or a placebo treatment with 0.9 % NaCl. Routine hoof trimming was performed in a tilt table and vital signs (rectal temperature (RT), heart rate (HR), respiratory rate (RR)), 33 different behavioral traits and blood cortisol concentrations were recorded throughout the experiment at six different time points (total of 55 min). The procedure itself elicited a clear stress response (increase in the RR, RT, defensive movements, lip twitching, swallowing, and flight behavior). Parallelly, the blood cortisol concentrations increased, reaching their maximum with 81.5 ng/ml in the control group when the sheep were tilted back into standing position. In the sedated sheep no increase in the RR and RT and a decrease in the HR was observed. Also, the behavioral signs showed a decrease in flight, defensive and general stress behavior (decrease in licking, movement of head and legs, and sitting on knees), complemented by the serum cortisol concentrations showing a 2.28 times reduced concentration at the end of the procedure, compared to the control sheep. The results confirm our hypothesis and support the conduction of future trials investigating the feasibility and benefit of a sedation of sheep prior to routine hoof trimming under practical circumstances.